Monocyte-macrophage dialogue with adipocytes : implication in human obesity-related type 2 diabetes - Hruskova, Zuzana (2016)
Mice studies in obesity-induced metabolic disease indicate a major role for monocytes/macrophages, whereas their contribution in regulating this disease in humans is not clear. To this end, we investigated the crosstalk between human monocytes and adipocytes in human obesity and Type 2 Diabetes (T2D). Co-culturing human monocytes with subcutaneous/omental adipocytes increased the expression of measured genes at the basal level. When polarized with IFNγ+LPA or IL-4, the cocultured monocytes showed impaired expression of inflammatory genes (e.g. IL6, IL1B, IL12p40), but upregulation of non-inflammatory genes (CCL18, CCL17). This was true for co-cultures with adipocytes from obeseT2D, but not overweight subjects. In contrast, irrespective of their origin, adipocytes co-cultured with monocytes upregulated inflammatory genes expression. An increased concentration of CCL18 and CCL17 was also detected in the culture supernatant from monocytes that were co-cultured with adipocyte conditioned media from obese-diabetic subjects, confirming our gene expression data. Interestingly, in vivo plasma of obese-diabetic subjects showed an approximately two-fold increase in CCL18 levels and CCL18 expression correlated with fasting plasma glucose, suggesting its possible role in obesity-T2D. Collectively, we demonstrate that human monocytes upon interaction with adipocytes displayed impaired response to inflammatory or microbial stimuli (IFNγ+LPA) and polarized to an M2-like phenotype, characterized by increased CCL18 expression that was detectable in vivo in adipose tissue and plasma. Interestingly, this is contrary to what is known in the mouse system.